Broadband echosounder measurements of the frequency response of fishes and euphausiids in the Gulf of Alaska. (13th November 2017) - Bassett, Christopher; De Robertis, Alex; Wilson, Christopher D; ,
Abstract: Broadband acoustic scattering techniques are not widely used in fisheries acoustics, but this may change due to the recent commercial availability of a broadband echosounder system operating at frequencies commonly used in fisheries surveys. A four-channel (15–150 kHz) broadband echosounder was used to investigate the potential of broadband methods to improve species discrimination during a walleye pollock ( Gadus chalcogrammus ) survey in the Gulf of Alaska. Narrowband echosounders combined with mid-water and bottom trawls were used to identify aggregations of interest for broadband measurements. Broadband frequency responses were measured for multiple pelagic and semi-demersal fishes as well as euphausiids. No clear patterns in the broadband frequency responses were identified that would aid in discrimination among the commonly encountered swimbladder-bearing species. The results are consistent with narrowband observations and suggest that both techniques face the same challenges when attempting to discriminate among acoustically similar species as frequency responses overlap within the measured bandwidth. However, examples are presented in which broadband frequency responses provide additional information about near-resonant scatterers. The benefits of broadband operations have not been fully realized and widespread adoption of broadband techniques and improved processing algorithms may yield improved acoustic-based species discrimination for use during fisheries surveys.